The Classıfıcatıon Of Functıonal Orthopaedıc Applıances In Our Opınıons - Ertuğrul Erdoğan; Eray Erdoğan (Galenos Yayinevi, 1989)
Appliances which are used for functional orthopedic therapy, is called as functional orthopedic appliances. So far, it has been constructed many appliances for functional treatment. But among these appliances, only activators were classified by STOCKFISH, H. in terms of construction speciality at his laboratory. Whole functional appliances were arranged by GÜRSOY, N. and PERKÜN, F. according to the organ which their functional balance pas spoiled by these appliances (according to the soft and hard tissue of organs) and PROFFIT, W. classified functional appliances in terms of the tissues which support them. In fact, these appliances should be classified according to the force they apply and their effect mechanism. Classification of functional appliance according to the force they apply: I- Pure functional appliance, II- Mechano-functional appliance. I- Pure functional appliance: A) Activators, B) Regulators. II- Mechano-functional appliance: A) Fixed, B) Removable. Classification of functional appliances according to the their effect mechanism: I- Activators, II- Regulators. I- Activators are separated two: A) Pure functional, B) Mechano-functional, and these are divided into sub-divisions. II- Regulators are separated three: A) Oral screens, B) Lip bumpers, C) Frankel appliance (4 type). We believe that, every two classification which were shown before at two charts, will be useful to our colleagues.